Unpacking the policy implementation in Islamic schools: A case of MAN 1 Kudus Indonesia - Abadi, Nur; Alfayn, Mukhammad Akhmad Najich (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2025)
This qualitative case study investigates the complex dynamics of policy implementation within Islamic educational institutions in Indonesia, focusing on the "madrasah unggul" (excellent madrasah) policy at MAN 1 Kudus. The study's purpose is to unpack how national directives are operationalized at the school level, examining the interplay between government mandates and institutional leadership. Employing a qualitative case study design, data were collected through in-depth, semi-structured interviews with key informants, including the kabid (head of the Islamic education division at the regional office) and the headmaster of MAN 1 Kudus, supplemented by document analysis and non-participant observations. Key findings, analyzed through Edward III’s model, reveal that successful implementation is driven by a highly effective, two-way communication flow, robust and strategically managed human and financial resources, and a strong, proactive disposition among implementers. Furthermore, an adaptive bureaucratic structure, characterized by collaborative problem-solving rather than rigid enforcement, significantly facilitates policy execution. While the school demonstrates exemplary resource mobilization and commitment, emerging concerns regarding educator workload highlight areas for continuous improvement. The study concludes that effective policy implementation in such hybrid educational settings hinges on adaptive governance and strong stakeholder collaboration, providing valuable insights for policymakers and school leaders. Despite its specific institutional focus, this research underscores universal principles for enhancing educational reforms in diverse contexts.